Structural behaviour of tyre-bale sandwich wall under axial load. (June 2021) - Awan, Abdul Basir; Shaikh, Faiz Uddin Ahmed
Abstract: This paper presents structural behaviour of tyre-bale sandwich wall that is made of two outer reinforced concrete walls and tyre-bale as core material. The thickness of tyre-bale and each concrete wall is 650 mm and 125 mm respectively. The concrete walls are reinforced with 6 mm diameter steel bars in each direction. Four sandwich walls were casted and tested on full scale under different compression loadings. In the first test, the axial load was applied directly to the tyre-bale to investigate the tyre-bale compressibility. The effect of eccentric loading was studied in the second test by applying the compression load on one concrete wall. In the third test, load was applied simultaneously on both concrete walls and finally, the fourth compression test was conducted by cutting-off the tie wires to simulate the severe corrosion conditions. The structural behaviour of sandwich wall is discussed in terms of ultimate load, vertical and lateral deflections, strain distribution and failure mechanism. In addition, the change in structural behaviour of sandwich wall under the effect of severe corrosion is presented. A significant reduction in structural capacity of sandwich wall was observed, when simulating corrosion conditions. Finite element modeling (FEM) of the sandwich wall was conducted in ABAQUS to simulate the damage of concrete in compression using concrete damage plasticity model. The difference in experimental and FEM results was found to be 15%. Furthermore, the experimental peak loads are compared with the existing empirical equations, which provided conservative design values to estimate the ultimate design load of sandwich wall.